Preservação e patrimônio no instituto histórico e geográfico de São Paulo (1894-1937) - Ferreira, Antonio Celso [UNESP]; MAHL, Marcelo Lapuente (Universidade Estadual Paulista (Unesp), 2011)
O Instituto Histórico e Geográfico de São Paulo, inaugurado no ano de 1894, foi um dos mais importantes espaços de formulação ideológica das elites intelectuais paulistas, na virada do século XIX. Ao longo da primeira república, esses associados produziram um vasto e eclético conjunto de artigos, unindo, de forma bastante singular, beletrismo e erudição com os paradigmas científicos próprios de sua época. Além disso, os sócios do IHGSP, localizados em um período anterior à consolidação dos espaços acadêmicos, também discutiram aspectos da preservação do patrimônio local e regional, inserindo-os em uma lógica própria de valorização da história e da civilização bandeirante, como um modelo de ação e atuação a ser admirado e seguido por todo o país.

The Institute of History and Geography in São Paulo, inaugurated in 1894, was one of the most important places for the ideological formulation of the intellectual elites in the State of Sao Paulo at the turn of the 19th century. Throughout the first republican government, those members produced a huge and eclectic amount of articles, fusing, in a very unique way, fine arts and scholarship with the scientific paradigms peculiar to that period. Furthermore, the Institute of History and Geography’s members, coming from a period prior to the consolidation of academic spaces, also discussed aspects of the preservation of local and regional heritage, including them within a customized schema of the recognition of their history and the explorer’s way of life, as an example of action and actualization to be admired and followed by the whole country.
Preservation and heritage at the São Paulo history and geography institute (1894-1937)
Keywords: Intellectual Life. Paulista Heritage. Cultural History; Vida Intelectual. Patrimônio Paulista. História Cultural